Paremiologia a stylistyka - Szpila, Grzegorz (Stylistyka, 2021)
In the paper the author puts forward basie tenets of paremiostylistics - a study of the sty listic values of proverbs in literary texts. The author suggests that proverbs be analysed as stylistic devices separately from other phraseological units due to their having specific and unique features. However, the author emphasises the similarities between proverbs and other fixed expressions, which makes his comments on proverbs applicable to an ana- lysis of other phraseological units as well. In the paper the author discusses, among other things: paremic style, paremic selection, the use of canonical forms of proverbs and their modifications, paremic allusion, functions of proverb in literary texts. His illustrative materiał comes from Salman Rushdie’s novels, which are remarkably phraseological. The author postulates that quantitative and qualitative methods be used in analyses of proverbs in literary texts.